PENGINTEGRASIAN PENDIDIKAN KARAKTER DALAM AKTIVITAS PEMBELAJARAN BAHASA INGGRIS - Annisa Astrid (Ta'dib: Jurnal Pendidikan Islam, 2012)
The current social problems are often related to the failure in building in our education process, more specifically teaching and learning process. Meanwhile, the basic concept of education is more than just transmitting knowledge to the learners but providing opportunities for the learners to build their character. Character education should be integrated into all subjects the students learn, including English as a Foreign Language (EFL). In setting up the objectives, it is important to provide students with learning activities and exercises which build character such as allowing students to understand the importance of respecting others or introducing responsibility. Such activities could be applied in all language learning activities. Accordingly, this paper tries to describe the integration of character education into language learning activities. Integrating character education into language activities should be started just from the initial process of designing curriculum.